ChemInform Abstract: Zirconocenes vs. Alanes: A Crucial Choice of the Allyl Source for Highly Diastereoselective Allylzincation of Nonracemic Chiral Imines. Issue 37 (August 2016) - Coffinet, Michael; Jaroschik, Florian; Vasse, Jean‐Luc
Abstract: A diastereoselective synthesis of enantioenriched homoallyl amine derivatives (III) and (V) is developed.